Strengthening Accessibility and Inclusivity in Libraries: The Role of Adaptive Technology in Supporting Visually Impaired Users - Purnomo, Gabriel Wahyu; Rizki Wikandani, Prayoga (Brawijaya University Library, 2024)
Libraries have long been recognized as key institutions in democratizing access to knowledge and information, yet users with visual impairments still face significant barriers to accessing these resources. The purpose of this research is to explore how adaptive technologies can improve accessibility and inclusivity in libraries for users with visual impairments. Using a qualitative methodology involving in-depth interviews and content analysis of library websites, this study assessed the effectiveness of current adaptive technologies and identified barriers to their use. The results show that, although adaptive technologies such as screen readers and indoor navigation systems hold great potential to improve user experience, there are still gaps in implementation and library staff awareness of the specific needs of visually impaired users. The conclusions of this study emphasize the importance of holistic integration of adaptive technologies in library service strategies to ensure equal access. Based on these findings, this paper recommends better staff training, the development of strong inclusive policies, and collaboration with disabled people's organizations to improve the accessibility and inclusiveness of libraries, thus supporting wider social participation of visually impaired users.